Problem based Learning: Its effect on problem solving skills of Islamic Boarding School student - Teuku Rizki; Miza Nina Adlini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
Increasing problem-solving competence is fundamental for students to learn in the future. The application of problem-based learning (PBL) has not been optimal, especially in Islamic boarding schools. This study aims to know the effect of PBL learning model on problem-solving skills of students in Islamic boarding schools. The type of research used is quasi-experimental research. The populations in this study were 4 classes with a total of 108 students. The sample consisted of 2 classes, namely class X IPA A as the experimental class and class X IPA B as the control class, 26 students each. The sampling technique used cluster random sampling. Data collection techniques using test instruments in the form of multiple choice with 25 questions. The data analysis technique used in this study was the normality test, homogeneity test, and hypothesis testing. The results were tested using a paired sample test (t test) on the PBL learning model on problem-solving skills, the significant value was 0.000 (sig. <0.05) then H0 is rejected and Ha is accepted. These results indicate a significant difference using the PBL model compared to conventional learning. PBL is an alternative learning model that encourages student-oriented biological learning and improves students' ability to solve problems, especially in Islamic boarding schools.Abstrak Peningkatan kompetensi pemecahan masalah menjadi hal mendasar bagi siswa untuk belajar di masa depan. Penerapan pembelajaran berbasis masalah (PBL) belum optimal khususnya di Pesantren.Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran PBL terhadap kemampuan memecahkan masalah pada siswa di pesantren. Jenis penelitian yang digunakan adalah penelitian eksperimen semu. Populasi dalam penelitian ini adalah 4 kelas dengan jumlah 108 siswa. Sampel terdiri atas 2 kelas yaitu kelas X IPA A sebagai kelas eksperimen dan kelas X IPA B sebagai kelas kontrol, masing-masing kelas terdiri atas 26 siswa. Teknik pengambilan sampel menggunakan cluster random sampling. Teknik pengumpulan data menggunakan instrumen tes berupa 25 soal pilihan berganda. Teknik analisis data penelitian ini menggunakan uji normalitas,uji homogenitas, dan uji hipotesis.Hasil penelitian diuji menggunakan paired sample test (uji t) pada model pembelajaran PBL terhadap kemampuan memecahkan masalah, diperoleh nilai signifikan 0,000 (sig.<0,05) maka H0 ditolak dan Ha diterima. Hasil tersebut menunjukkan adanya perbedaan signifikan dengan menggunakan model pembelajaran PBL dibandingkan dengan pembelajaran konvensional. PBL sebagai alternatif model pembelajaran yang mendorong pembelajaran biologi berorientasi siswa serta meningkatkan kemampuan siswa dalam memecahkan masalah khususnya pada siswa Pesantren.